Weekday sunlight exposure, but not vitamin D intake, influences the association between vitamin D receptor genotype and circulating concentration 25‐hydroxyvitamin D in a pan‐European population: the Food4Me study. Issue 2 (11th November 2016) - Livingstone, Katherine M.; Celis‐Morales, Carlos; Hoeller, Ulrich; Lambrinou, Christina P.; Moschonis, George; Macready, Anna L.; Fallaize, Rosalind; Baur, Manuela; Roos, Franz F; Bendik, Igor; Grimaldi, Keith; Navas‐Carretero, Santiago; et al.
Abstract : In a cross‐sectional study of 1312 European adults, it is observed that individuals who carry the minor allele for the vitamin D receptor gene have lower circulating 25(OH) vitamin D concentration than those who do not carry the minor allele. This relationship appears to be modified by weekday sunlight exposure but not dietary vitamin D intake. . Abstract : Scope: Little is known about diet– and environment–gene interactions on 25‐hydroxyvitamin D (25(OH)D concentration. This cross‐sectional study aimed to investigate (i) predictors of 25(OH)D concentration and relationships with vitamin D genotypes and (ii) whether dietary vitamin D intake and sunlight exposure modified these relationships. Methods and results: Participants from the Food4Me study ( n = 1312; age 18–79) were genotyped for vitamin D receptor ( VDR ) and vitamin D binding protein at baseline and a genetic risk score was calculated. Dried blood spot samples were assayed for 25(OH)D concentration and dietary and lifestyle information collected. Circulating 25(OH)D concentration was lower with increasing genetic risk score, lower in females than males, higher in supplement users than non‐users and higher in summer than winter. Carriage of the minor VDR allele was associated with lower 25(OH)D concentration in participants with the least sunlight exposure. Vitamin D genotype did not influence the relationship between vitamin D intake and 25(OH)D concentration. Conclusion: Age, sex, dietary vitamin D intake, country, sunlight exposure, season, and vitamin D genetic risk score were associated with circulating 25(OH)D concentration in a pan‐European population. The relationship between VDR genotype and 25(OH)D concentration may be influenced by weekday sunlight exposure but not dietary vitamin D intake.